Is Prior Experience with Social Problem Related to Social Entrepreneurial Intentions in Teenagers and Young Adults: A Literature Review - Fransiska Krisnaningtyas; Triana Noor Edwina Dewayani Soeharto (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The growing need for social entrepreneurship to help solve various social problems has prompted a lot of research on social entreneurship.the factor that can influence the formation of social entrepreneurial intentions are also widely studied. One of the influencing factors is prior experience.prior experience means that a person has been in direct contact with social issues or has experience working as a volunteer with social organizations. Therefore, the literature study aims to review whether prior experience with social problems is related to entrepreneurial intentions in teenagers and young adults. Furthermore, in the analysis process, this research uses the literature study method by collecting various sources from scientific journals, scientific articles, books related to research variabies the result were obtained from the analysis of research result from 15 journais published from 2017-2021. The results showed that prior experience related to social problems influence social entrepreneurial intentions.